The Effect of Seed Position in Pod on The Seed Viability of Cowpea (Vigna unguiculata) - Mochammad Muchlish Adie; Ayda Krisnawati; Ratri Tri Hapsari (Biosaintifika: Journal of Biology & Biology Education, 2019)
In Indonesia, cowpea (Vigna unguiculata L. Walp) is widely cultivated in the dry climate area. Famers used the seeds from previous plants or traditional markets. The aims of the study were to determine the effect of seed position in the pods on seed viability and to study the seed and seedling characteristics regarding the genetic variation and seed position. The cowpea used in this study was from 18 Indonesian local varieties. Twenty-five matured pods were randomly detached from each variety. Each pod was divided into three parts, i.e. the lower third (base), the middle third, and the upper third (tip). The seeds of each part were germinated using sand media to evaluate their viability. Each local variety has different response to the percentage of seed viability in each seed position in the pod. The highest abnormal germination occurred in the seed from lower part of the pod, followed by seed in the middle of the pod and the tip of the pod. The variation of seed viability in pods was more determined by genetic differences in local varieties. The average seed viability from three parts of the pods was highest for seeds originated from local varieties of Lumajang and Sampang. Therefore, it is recommended that the seeds of both local varieties can be mixed to be used for optimum cowpea cultivation.Â